Correlation among cap design, gripping technique and age in the opening of squeeze-and-turn packages: A biomechanical study - Bonfim, Gabriel H.C. [UNESP]; Medola, Fausto O. [UNESP]; Paschoarelli, Luis C. [UNESP] (Elsevier, 2016)
Child-Resistant Packagings (CRPs) are important because they prevent children accessing potentially harmful products. However, the locking mechanism located on the caps still presents usability problems, especially for elderly users. The aim of this study was to evaluate the effects of packaging design, gripping technique and age in the transmission of torque when opening packages with squeeze-and-turn closures. Three different packages of mouthwashes (squeeze-and-turn type) were analyzed and two gripping techniques were used: tridigital and bidigital. The sample comprised one hundred subjects across five age groups equal in size (3–5 years; 8–12 years; 13–17 years; 30–59 years; over 60 years). For maximum torque measurement, the packages were adapted to receive a torquimeter internally installed and connected to the cap. The results show that packaging design, gripping technique and age are factors that influence the transmission of torque when opening squeeze-and-turn packages. In terms of the packaging design, the cap with the largest diameter allowed the application of higher torques. The opening process using the tridigital gripping presented higher values than the bidigital. In terms of the relative strength of grip across the age groups, children from 3 to 5 years presented the lowest torque values. However, the torque transmission with tridigital grip for children under 5 years old was higher when compared to the bidigital grip for all groups and packagings. The current findings provide biomechanical data on opening squeeze-and-turn packages, contributing to the design of packages that best balance safety and usability.
Keywords: Biomechanics; Ergonomics; Packaging openability